Phenotypic and Transcriptomic Analyses Demonstrate Interactions between the Transcriptional Regulators CtsR and Sigma B in Listeria monocytogenes - Hu, Yuewei (American Society for Microbiology (ASM), 2007)
Listeria monocytogenes σ(B) positively regulates the transcription of class II stress response genes; CtsR negatively regulates class III stress response genes. To identify interactions between these two stress response systems, we constructed L. monocytogenes ΔctsR and ΔctsR ΔsigB strains, as well as a ΔctsR strain expressing ctsR in trans under the control of an IPTG (isopropyl-β-d-thiogalactopyranoside)-inducible promoter. These strains, along with a parent and a ΔsigB strain, were assayed for motility, heat resistance, and invasion of human intestinal epithelial cells, as well as by whole-genome transcriptomic and quantitative real-time PCR analyses. Both ΔctsR and ΔctsR ΔsigB strains had significantly higher thermotolerances than the parent strain; however, full heat sensitivity was restored to the ΔctsR strain when ctsR was expressed in trans. Although log-phase ΔctsR was not reduced in its ability to infect human intestinal cells, the ΔctsR ΔsigB strain showed significantly lower invasion efficiency than either the parent strain or the ΔsigB strain, indicating that interactions between CtsR and σ(B) contribute to invasiveness. Statistical analyses also confirmed interactions between the ctsR and the sigB null mutations in both heat resistance and invasion phenotypes. Microarray transcriptomic analyses and promoter searches identified (i) 42 CtsR-repressed genes, (ii) 22 genes with lower transcript levels in the ΔctsR strain, and (iii) at least 40 genes coregulated by both CtsR and σ(B), including genes encoding proteins with confirmed or plausible roles in virulence and stress response. Our data demonstrate that interactions between CtsR and σ(B) play an important role in L. monocytogenes stress resistance and virulence.